The Role of Leaders’ Emotional Sincerity towards Followers’ Trust: Leaders’ Integrity & Quality Relationship - Nisar, Qasim Ali; Hameed, Waseem ul; Basheer, Muhammad Farhan; Basheer, Muhammad Farhan; Hussain, Muhammad Sajjad; Waqas, Ali (The journal of contemporary issues in business and government, 2021)
This study focused on the belief that followers assess the emotional sincerity of their leaders andconsequently, it affects to followers’ perceived trust and their behaviors.It identified the key role of leaders’ emotional sincerity towards followers’’ outcomes (leaders integrity, quality relationship and trust in leaders).This studyproposed a theoretical model on the basis of underpinning theory and empirical evidence. On the basis of literature support and underpinning theories, it is proposed that followers’ perceived emotional sincerity may a significant predictor andsignificantly influence to their leaders’ integrity and relationship quality. Moreover, leaders’ integrity and relationship quality (between leaders and followers) may affect followers’ trust in their leaders. Future studies may empirically test this model to gain insight understanding regarding the role of leaders’ emotional sincerity to shape the followers’ behaviors.